Effects of protease supplementation and diet type on jejunal and ileal digestibility and total tract metabolisability of nitrogen, starch, and energy in broilers. Issue 3 (4th May 2022) - McCafferty, K. W.; Toghyani, M.; Morgan, N. K.; Cowieson, A. J.; Choct, M.; Moss, A. F.
ABSTRACT: 1. A study was conducted to assess the effects of supplemental protease (0 or 15, 000 units/kg) and diet type (maize- or wheat-based) on apparent jejunal and ileal digestibility and apparent total tract metabolisability of nutrients in Cobb 500 mixed-sex broilers from 6 to 31 d of age. 2. Birds were randomly distributed into 56 metabolism cages (6 birds/cage; 14 replicates/treatment). At 22 d of age, jejunal and ileal digesta contents were collected and pooled from 4 birds/cage to determine apparent digestibility coefficients (DC) and digestible energy (DE). Feed intake was measured, and total excreta were collected from 8 to 11 and 18 to 21 d of age to determine apparent metabolisable energy (AME) and total tract nitrogen and starch metabolisability coefficients. 3. Broilers offered the maize-based diet with protease had greater (P < 0.05) jejunal nitrogen DC, starch DC, and DE (8.2, 6.5, and 14.9%, respectively) and ileal nitrogen DC and DE (5.1 and 6.8%, respectively) than those offered the maize-based diet without protease. Ileal starch DC was increased (P < 0.05) by 1.1% with protease supplementation. 4. Broilers offered maize-based diets had greater (P < 0.05) nitrogen (7.3%) and starch (0.6%) metabolisability coefficients and AME (4.7%) from 8 to 11 d of age, and nitrogen (4.3%) metabolisability coefficients and AME (2.0%) from 18 to 21 d of age compared with those offered wheat-based diets. 5. Thus, protease supplementation and diet type can affect digestive dynamics and nutrient utilisation in broilers.